Prevalence of toxoplasmosis and its association with dementia in older adults in central Africa: A result from the EPIDEMCA programme - (:unkn) unknown (My University, 2018)
OBJECTIVE:We aimed at estimating the seroprevalence of Toxoplasma gondii infection in older adults living in Central Africa and investigating its association with dementia using data from the Epidemiology of Dementia in Central Africa (EPIDEMCA) programme.METHODS:A cross-sectional multicentre population-based study was carried out among participants aged 73 (±7) years on average, living in rural and urban areas of the Central African Republic and the Republic of Congo between November 2011 and December 2012. Blood samples were collected from each consenting participant. The detection of anti-T.gondii immunoglobulin G antibodies was performed in 2014 in France using a commercially available ELISA kit. Participants were interviewed using a standardized questionnaire including sociodemographic characteristics. DSM-IV criteria were required for a diagnosis of dementia. Multivariate binary logistic regression models were used to estimate the association between toxoplasmosis infection and dementia.RESULTS:Among 1,662 participants, the seroprevalence of toxoplasmosis was 63.0% (95% confidence interval (CI): 60.7-65.3) overall, 66.6% (95%CI: 63.4-69.8) in Central African Republic and 59.4% (95%CI: 56.1-62.7) in the Republic of Congo. In multivariate analyses, toxoplasmosis status was significantly associated with increasing age (p=0.006), Republic of Congo (p=0.002), urban area (p=0.001) and previous occupation (p=0.002). No associations between dementia and toxoplasmosis status or anti- T.gondii IgG titres were found.CONCLUSION:T.gondii infection was not associated with dementia among older adults in Central Africa. Our findings are consistent with previous studies and add to the knowledge on the relationship between T.gondii infection and neurological disorders. This article is protected by copyright. All rights reserved.
Keywords: African Research